Mercado, política e cultura na “baixa” Amazônia: circuitos longos e curtos - CASTRO, Fábio Fonseca de (Escola Superior de Propaganda e Marketing, 2022)
This article discusses the cultural circuits present in the space of “low” Amazon - the more consolidated área, in the region, in terms of their West ern occupation - with reference to three population groups, here understood as social trajectories, which differ among themselves by their way of economic and cultural occupation of space. We observe as two of these social trajectories partici pate more actively in cultural circuits, while the third shows up more reserved. We propose to interpret these relations of closeness and distance from the intersubjec tive social experience that involves them.